2014
DOI: 10.5812/aapm.14989
|View full text |Cite
|
Sign up to set email alerts
|

The flow Rate Accuracy of Elastomeric Infusion Pumps After Repeated Filling

Abstract: Background:One of the frequent applications of elastomeric infusion pumps is postoperative pain management. In daily practice, the disposable pumps get refilled with modified medication combinations in the successive days; although, the accuracy of infusion rates is unknown to clinicians.Objectives:Our aim was to evaluate the effect of repeated filling on the delivery rate accuracy of an elastomeric pump available in our market.Materials and Methods:We examined 10 elastomeric infusion pumps (BOT-802, Nanchang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…The temperature of the solution in the elastomeric infusor on a patient has not been previously reported although some studies showed that most manufacturers calibrated the pumps at 31-32 C to simulate the expected normal skin temperature, 20,21 mainly for the concern of temperature-dependent infusion rate. Here we carefully designed and measured the change of temperature of solutions inside the infusor during 24 h period worn by different volunteers and report the range measured including the highest temperature of 33.5 C which was lower than this evaluated temperature for stability studies of 35 C, demonstrating its validity.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature of the solution in the elastomeric infusor on a patient has not been previously reported although some studies showed that most manufacturers calibrated the pumps at 31-32 C to simulate the expected normal skin temperature, 20,21 mainly for the concern of temperature-dependent infusion rate. Here we carefully designed and measured the change of temperature of solutions inside the infusor during 24 h period worn by different volunteers and report the range measured including the highest temperature of 33.5 C which was lower than this evaluated temperature for stability studies of 35 C, demonstrating its validity.…”
Section: Discussionmentioning
confidence: 99%
“…The driving pressures in these pumps are from 260 to 520 mmHg, and the infusion rates can vary from 0.5 to 500 ml/h. [ 66 ] The delivery rates are limited to the set values due to the presence of flow restrictors. The variable rate infusor can be adjusted to deliver 5, 7, or 12 ml/h drug, whereas the fixed infusors are designed to deliver 1.5, 2, 5, 7, and 12 ml/h of the drug volume.…”
Section: Postoperative Pain Reliefmentioning
confidence: 99%
“…Elastomeric pumps are particularly popular due to their ability to be refilled, low cost, portability, independence from a power supply, disposability, as well as high patient satisfaction. 35 However, it has been suggested that these pumps may deliver inconsistent volume which could lead to inadequate analgesia or unintended side effects. 6,7 Such disadvantages can be caused by a multitude of factors such as temperature changes, viscosity of infused fluid, and even the height of the elastomeric pump relative to the catheter site.…”
Section: Introductionmentioning
confidence: 99%